Creatine and creatinine quantification in olympic athletes: dried blood spot analysis pilot study - Bachini, I. F.; Pereira, D.; Santos, R.; Hausen, M.; Pereira, G.; Vieira, C.; Taylor, L.; Pegurier, M. (Biology of Sport, 2022)
Capillary dried blood spot (DBS) samples facilitate field-based collection without venipuncture. This pilot study aims to evaluate the viability of creatine (Cr) and creatinine (Crt) quantification using fresh capillary serum (CrS/CrtS) and DBS samples (CrDBS/CrtDBS), using Flow Injection Analysis Mass Spectrometry (FIA - MS). Nine Olympic Athletes provided a capillary blood sample to assess CrS/CrtS and CrDBS/CrtDBS quantified by FIA - MS. No difference between CrtS (mean ± SD: 813.6 ± 102.4 µmol/L) and CrtDBS (812.4 ± 108.1 µmol/L) was observed with acceptable variance [SEM 88.7; CV 10.7%; ICC 0.57 (CI 95% 0.06 - 0.84)] and agreement [very strong (Spearman: r = 0.77; p < 0.01) or strong (Pearson: r = 0.56; p = 0.04); Bland Altman: lower (-193) and upper (+196) limits of agreement]. CrS (mean ± SD: 691.8 ± 165.2 µmol/L) was significantly different to CrDBS (2911 ± 571.4 µmol/L) with unacceptable variance [SEM 171.6; CV 27%; ICC 0.002 (CI 95% -0.02 - 0.07)] and `weak` agreement [Spearman: r = 0.21, p = 0.47 and Pearson: r = 0.06, p = 0.84; Bland Altman lower (-3367) and upper (-1072) limits of agreement]. Crt quantification is viable using both CrtS and CrtDBS (but not for Cr and CrS/CrDBS), with the DBS tissue handling technique offering several methodological and practice facing advantages. Future work should expand upon the sample size, explore sport/discipline relevant analytes across a full competitive season, including key training, recovery and performance blocks of their periodized performance plan.